2005
DOI: 10.1093/carcin/bgi308
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new retinoids in the prevention of mammary cancers and correlations with short-term biomarkers

Abstract: A number of retinoid X receptor (RXR) agonists have proven to be highly effective in preventing methylnitrosourea (MNU) induced mammary cancers. However, these agonists have side effects; particularly causing an increase in serum triglyceride levels. A series of ligands for RXR were designed based on computer modeling to the ligand binding domain (LBD) of the RXR receptors and on structure-activity relationships. The chemopreventive effects of these retinoids were evaluated in the relatively long-term MNU mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
97
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 22 publications
5
97
0
1
Order By: Relevance
“…Its effectiveness by oral delivery was further demonstrated by our group where oral gavage of 180 mg/kg bexarotene significantly decreased small cell lung carcinoma incidence in a lungspecific Rb1 and p53 knockout model (23). However, and similar to the human situation, bexarotene delivered orally causes hypertriglyceridemia in rodents as well (24). Mice treated with 30 mg/kg bexarotene by oral gavage, a dose that shows minor efficacy in vinyl carbamate-induced mouse lung tumors, does increase plasma TG levels 2-fold (25).…”
Section: Discussionmentioning
confidence: 90%
“…Its effectiveness by oral delivery was further demonstrated by our group where oral gavage of 180 mg/kg bexarotene significantly decreased small cell lung carcinoma incidence in a lungspecific Rb1 and p53 knockout model (23). However, and similar to the human situation, bexarotene delivered orally causes hypertriglyceridemia in rodents as well (24). Mice treated with 30 mg/kg bexarotene by oral gavage, a dose that shows minor efficacy in vinyl carbamate-induced mouse lung tumors, does increase plasma TG levels 2-fold (25).…”
Section: Discussionmentioning
confidence: 90%
“…We have demonstrated that 9cUAB30 compared well with Targretin in its capacity to prevent mammary cancer (21)(22)(23)(24)(25). The in vitro studies presented here also show how similar each rexinoid is in blocking ErbB2-oncogenic transformation, consistent with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although 9cUAB30 is slightly less potent than Targretin or 9cRA, it displays a higher degree of RXR selectivity. 9cUAB30 has also been shown to be effective in cancer prevention models (21)(22)(23)(24)(25). 9cUAB30 is a tissue-selective RXR agonist; it does not act as an agonist in liver to activate lipid biosynthesis although it has agonist capabilities in cancer cells (26).…”
mentioning
confidence: 99%
“…One group of end points is the effects of short-term exposure to agents on proliferation and apoptosis in small palpable mammary cancers. These end points have been used in examining a wide variety of agents, including aromatase inhibitors, selective ER modulators, and farnesyltransferase inhibitors (18), as well as in screening a variety of RXR agonists for chemopreventive activity (19). An excellent correlation was found between decreases in proliferation and increases in apoptosis and long-term chemopreventive and therapeutic efficacies.…”
Section: Introductionmentioning
confidence: 99%